Jeevaniya Mahakashay And Its Immunomodulator Effect: A Review Article - Nagar, Dhanraj; Sharma, Manoj Kumar (International Research Journal of Ayurveda & Yoga, 2020)
India has the third largest HIV in the year 2016 and 2nd largest in SARS COVID 19 in the year 2020 of epidemic in the world.In HIV prevalence in India was an estimated 0.3%. This equates to 2.1 million people living with and COVID 19 cases prevalance are .586% which is equates to 8.0 milion people living with SARS COVID19 infection . HIV as well as COVID 19 infections affects multisystem, chiefly the Immune System which can be corrected to OjaKhasya Rasayana Chikitsa is the frontline therapy employed to treat Ojas disorder. For the process of rejuvenation, Ayurveda has described a unique therapy-Rasayana therapy. Drugs described under Rasayana act on Agni, Dhatu and Srotas level and help in formation of prashasta dhatus maintaining a perfect equilibrium of all the doshas and dhatus. Jeevaniyagana is mentioned in Charak Samhita sutrasthana chapter fourth Shad virechanashatashritiyaadhyay. Charakokta Jeevaniya Mahakashay- Jeevak, Rishabhaka, Meda, Mahameda, Kakoli, Ksheerakakoli, Mudgaparni, Mashaparni, Jeevanti, Madhuk. Detail usage of the individual drugs of Jeevaniyagana has been mentioned in the article and its role as immunomodulator has been discussed. Jeevaniyagana now a days used as-Shatavari, Vidari, Ashwagandha, Mudgaparni, Mashaparni, Jeevanti, and Madhuk.